MO736: The Role of Uremic Retention Solutes in the MIA Syndrome in Haemodialysis Subjects. (3rd May 2022) - Ciceri, Paola; Artioli, Luisa; Magagnoli, Lorenza; Barassi, Alessandra; Galassi, Andrea; Gennaro Cozzolino, Mario
Abstract: BACKGROUND AND AIMS: In end-stage renal disease (ESRD), the high morbidity and mortality risk for cardiovascular disease (CVD) is not easily explained only on the basis of traditional factors. Among non-traditional ones, malnutrition, inflammation and atherosclerosis/calcification have been described as the 'MIA syndrome'. METHOD: In this study, we evaluated the association between the variation in serum levels of 27 uremic retention solutes plus 6 indexes related to the MIA syndrome processes in dialysis patients. Uremic retention solute levels were detected by the ELISA or using an ultra-performance liquid chromatography—tandem mass spectrometry method. The pro-calcifying, pro-apoptotic and pro-necrotic effects of uremic serum were evaluated in an in vitro model of high-Pi induced calcification in vascular smooth muscle cells (VSMC). RESULTS: As expected, we found reciprocal correlations between serum albumin, total cholesterol and phosphate, linking a better nutritional status with higher phosphate levels ( r = 0.37, r = 0.40, r = 0.54, respectively; P < 0.05). The relationship between malnutrition and inflammation is highlighted by the negative correlation of serum cholesterol levels with serum alpha-1 acid glycoprotein and IL-6 levels ( r = –0.56, r = –0.39, respectively; P < 0.05). These results suggest that the increase in inflammatory mediators is probably higher in malnourished patients, and a better nutritional state seems to correlate with lower inflammatory marker levels. Moreover, we found a significant direct correlation between alpha-1 acid glycoprotein and IL-6 with a correlation coefficient of 0.54 and P < 0.01, indicating that both these uremic toxins might participate in the maintenance of the inflammation. The relation between inflammation and atherosclerosis/calcification is supported by the correlations between IL-6 variations that significantly correlate with both PTX3 and VEGF ( r = 0.36 and r = 0.81; P < 0.05) and with VSMC in vitro high-Pi induced calcification ( r = 0.66; P < 0.01). Thus, IL-6, a regulator of acute phase protein synthesis, seems to be related to CVD markers (PTX3 and VEGF) and in vitro calcification, two robust indexes of increased cardiovascular risk. In addition, the Kyn/Try ratio directly correlates with serum FGF23 levels with a correlation coefficient r of 0.60 and P < 0.01. Regarding atherosclerosis/calcification, we found that PTX3, TMAO, IS, myoglobin and FGF23 correlate with each other in several combinations, reflecting the elevated cardiovascular risk present in ESRD. PTX3 shows a trend towards a direct correlation with TMAO ( r = 0.37 and P < 0.05), and IS shows a trend towards a direct correlation both with TMAO, FGF23 and myoglobin ( r = 0.46, r = 0.45 and r = 0.42; P < 0.05). Moreover, IS and TMAO correlate also with two processes strictly related to VSMC calcification, such as apoptosis and necrosis (IS: apoptosis r = 0.69 and necrosis r = 0.47; P < 0.05; TMAO: apoptosis r = 0.42 and necrosis r = 0.40 with P < 0.05). Finally, VEGF shows a robust correlation with in vitro calcification ( r = 0.74; P < 0.01). CONCLUSION: Among all the correlations found between uremic toxin variations in dialysis patients, IL-6 seems to have a central role correlating with malnutrition and several CV markers together with vascular calcification (VC). This might be explained by the characteristics of IL-6 being contemporary an inflammatory and a CVD marker in ESRD. On the other hand, IS has a potential role in VC, suggesting a central role of the uremic milieu in MIA syndrome development. Therefore, there is an urgent need to find a more efficient dialysis treatment to improve the clearance of uremic retention solutes in order to try to ameliorate CV outcomes in ESRD patients.